TrailGuard : advancing hiking footwear for optimal comfort and safety : a thesis presented in partial fulfilment of the requirements for a Master in Design at Massey University, Wellington, New Zealand - Martin, Austin (Massey University, 2023)
Tramping, known elsewhere as backpacking, rambling, hill walking or bushwalking, is a popular activity in New Zealand. Tramping is a uniquely New Zealand term and is defined as a recreational activity involving walking over rough country. The recent lifestyle developments and upgrading of many tracks in New Zealand have led to an increase in popularity within tramping. It is evident that this outdoor activity significantly contributes to injuries in adventure tourism in New Zealand. With recorded injured body parts being in the lower extremities of the body, this suggests that the type of footwear used on these walks may have an impact on the occurrence of injury among trampers. The aim of this practice-based design project is to develop a performance hiking footwear solution that has integrated pain/injury reducing features to sustain the user when hiking on rugged uneven terrain to elevate their user journey and experience. Through iterative design and research methodology, this project outlines how the redesign of hiking footwear can lead to an innovative solution that accommodates the users wants and needs when it comes to reducing pain, discomfort, and injury whilst on the trail. The design outcome consists of key componentry prototypes and an integrated system for hiking footwear. Understanding specified performance requirements and human physiology allows design to extract insight, advancing design technology for further development and application.
Keywords: 330309 Industrial and product design